Levers of control as a mediation on the relationship of the effect of financial performance and non-financial performance on managerial performance - Riski Hernando; Nora Triandini; Mukhzarudfa Mukhzarudfa; Rezi Abdurrahman (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2022)
This study examines the direct and indirect influence of the performance measurement system and levers of control on managerial performance. The research population is the manager or head of the section who leads a service and trading company located in Jambi City. The sample selection technique was carried out based on the specified criteria so that there were 103 respondents. Each respondent was asked to fill out a questionnaire and the data obtained were analyzed and processed with SEM-PLS WarpPLS 7.0 statistics. The results show that financial performance affects managerial performance, as well as non-financial performance. In addition, the two levers of control systems are also able to influence the relationship between performance measurement and managerial performance in Jambi City. The results of this study also contribute to the company's collaboration between the performance measurement system and the management control system.